Memoria archivada del chisme. Análisis de un caso de infidelidad mediática - Solís López, Augusto-Pavel (Pontificia Universidad Católica del Perú, 2024)
The article aims to analyze the discourse of infidelity gossip in a Peruvian show business couple, focusing on the construction of memory about infidelity in the social network X during the year 2024. A descriptive qualitative analysis technique is employed based on a selection of 115 highlighted tweets collected from the X API, with the terms Christian Domínguez and Pamela Franco. The analysis focuses on the categories of monogamy, cheating and infidelity information according to gender. The results indicate that there is a difference in the interpretation of the memory of infidelity in the case of Dominguez, with a greater scope and conversations that use humor as part of the discourse. In contrast, in the case of Franco, more judgments about his behavior are observed, as well as assessments related to his emotions and body, and a lower presence of humor. In conclusion, the mediatization of gossip in Peru does generate distinctions about who is considered unfaithful, influenced by gender and the personal history of each individual in relation to this behavior.

El artículo tiene como objetivo analizar el discurso del chisme de infidelidad en una pareja del espectáculo peruano, centrándose en la construcción de memoria sobre infidelidad en la red social X durante el año 2024. Se emplea una técnica de análisis cualitativo descriptivo basada en una selección de 115 tuits destacados y recopilados desde la API de X, con los términos Christian Domínguez y Pamela Franco. El análisis se enfoca en las categorías de monogamia, engaño e información sobre la infidelidad según el género. Los resultados indican que existe una diferencia en la interpretación de la memoria de infidelidad en el caso de Domínguez, con un mayor alcance y conversaciones que utilizan el humor como parte del discurso. En contraste, en el caso de Franco, se observan más juicios sobre su conducta, así como valoraciones relacionadas con sus emociones y su cuerpo, y una menor presencia de humor. En conclusión, la mediatización del chisme en el Perú sí genera distinciones en torno a quién es considerado infiel, y el género y la historia personal de cada individuo influyen en relación con esta conducta.
Archived Memory of Gossip. Analysis of a Case of Media Infidelity
Keywords: Infidelity; Memory; Archives; Mediatization; Gossip; Twitter; Infidelidad; Memoria; Archivos; Mediatización; Chisme; Twitter; https://purl.org/pe-repo/ocde/ford#5.09.01